Jamu Gummies: Innovation for women's health and productivity enhancement of the Sapta Marga village women's association - Mayang Murni; Rizky Nafaida; Muhammad Khalil (Universitas Muhammadiyah Magelang, 2024)
This community service program aims to improve women’s reproductive health while supporting the economic productivity of the PKK mothers in Sapta Marga Village, Aceh Tamiang Regency, through the innovation of jamu gummies. The program focuses on transforming rhizomes into practical, tasty, and economically valuable products. The methods implemented include educational sessions on the health benefits of rhizomes and a three-day intensive training covering the production, packaging, and marketing of jamu gummies. Evaluation results indicate a significant improvement in participants' knowledge and skills in rhizome processing, with an average understanding increase of over 80%. The jamu gummies produced are of high quality, meet marketing standards, and are ready to be sold through both digital and conventional marketing strategies taught during the program. The initiative also creates new economic opportunities for PKK mothers without disrupting their household responsibilities.